Jewish leadership in Roman Palestine from 70 CE to 135 CE - Choi, Junghwa, 1974- (Leiden : Brill, 2013)
Reconstructing Jewish political leadership of the late Second Temple and Talmudic periods, this book suggests that the period between two great revolts is the best period to study leadership dynamics.
Ch. 1. Introduction -- ch. 2. Jewish ideals of leadership -- ch. 3. Models of local control within the Roman world -- ch. 4. The extent of the realisation of Jewish ideals of leadership between 70 CE and 135 CE -- ch. 5. Roman control of Judaea from 70 to 135 CE -- ch. 6. Conclusion
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Jewish leadership -- Palestine; Palestine -- History -- 70-638.; Romans -- Palestine; HISTORY / Ancient / General; Electronic books